Inovasi Manajemen Sarana dan Prasarana dalam Memenuhi Standar Nasional Pendidikan Mewujudkan Generasi yang Kuat Keimanan dan Ekonomi - Ahmad Farid; Mudhofir Mudhofir; Subaidi Subaidi (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study is to find out innovations in the management of facilities and infrastructure in meeting national education standards to create a generation of strong faith and economy. In this study, the author uses qualitative research, namely research that intends to interpret phenomena that occur and are carried out in various ways involving various existing methods. This research includes descriptive research, because it aims to describe certain characteristics of a phenomenon and seeks to describe and interpret what exists (it can be about conditions or relationships that exist, opinions that are growing, ongoing processes, consequences or effects that occur, or trends that occur). In this case, it is about Management of Facilities and Infrastructure at MAN 2 Wonosobo in creating a generation that is strong in faith and economically. In this study, the main data source is the results of interviews with informants, which include the head of madrasah, deputy head of the facilities and infrastructure division. , the development team, as well as madrasa committees and other supporting informants.While the data used as sources of information are documents related to the management of facilities and infrastructure management, both regarding planning, procurement, utilization, and development techniques that have been carried out by MAN 2 Wonosobo. feeder This research data analysis using interview, observation, documentation, and data analysis techniques. The technique of checking data validation is by carrying out extended participation, diligent observation, and triangulation. Data analysis techniques with data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that in an effort to procure and develop facilities and infrastructure towards meeting national education standards, Aliyah Negeri 2 Wonosobo is a madrasa that is able to manage the potential and opportunities that exist, with limited government budget through DIPA for both procurement and maintenance, the madrasa has established policies To manage the existing budget effectively and efficiently, the concept of management is really applied, starting from planning, procurement, distribution, inventory, maintenance and elimination, so that the limited budget can be utilized to support the minimum standard of education services. Madrasah Aliyah Negeri 2 Wonosobo realizes the limitations that exist, it requires innovation steps to be able to continue to exist to meet the needs of the required facilities and infrastructure, the innovation steps taken include setting priority needs for facilities and infrastructure, utilizing existing facilities with low maintenance costs. available so that all appropriate suggestions will be put to good use again, optimizing the role of the madrasa committee and making efforts to apply for assistance to improve facilities and infrastructure through SBSN. The opportunity arises, namely maximizing the managerial role of the madrasah principal, mobilizing all madrasa human resources who are certainly very qualified because of their competence and performance, mobilizing the potential for internal cohesiveness to create breakthroughs and of course developing Constructive communication with all parties in order to bring in support and assistance to fulfill the facilities and infrastructure in madrasas. By using the various development potentials that exist in Madrasah Aliyah Negeri 2 Wonosobo, we are able to create a generation (graduates) with strong faith and economy.